The Conductor of Care: What is AI Orchestration in Hospitals? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
Introduction: From Fragmented Data to Harmonized Healthcare The modern hospital is a complex ecosystem, a symphony of interconnected processes, personne...
Keywords: Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care; Medical Ethics